Exploring the Supervision Experiences of LGBTQ+ Social Workers in Taiwan - Wang, Hui-Chi; Pan, Chia-Yen (Journal of Ecohumanism, 2024)
This study adopts an ecological systems perspective to explore the multifaceted experiences of LGBTQ+ social workers under workplace supervision. It examines how gender identity, workplace culture, social environment, and time influence their professional growth. The findings underscore the importance of supervisors' gender sensitivity in fostering psychological safety and professional development for LGBTQ+ social workers. While the implementation of gender-friendly policies can improve workplace conditions, their effectiveness is often constrained by institutional culture. Additionally, gender identity emerges as both a strength and a challenge in supervisory relationships, with client acceptance significantly impacting professional identity and competency. As Taiwan progresses in addressing diverse gender issues, LGBTQ+ social workers are learning to balance their identities with professional roles. This study fills a gap in research on the workplace experiences of LGBTQ+ social workers and provides practical recommendations for improving gender-friendly policies, enhancing supervisory practices, and fostering inclusive workplace cultures.